ICARUS – Virtual Reality based training for Assembly, Integration and Testing - Twigt, D.; Mathot, L.; Den Exter, E.; Lahkwani Daswani, M.; Brouwer, S.; Vos, C.; Caso, S.; Hove, P.E. ten (My University, 2025)
Satellite Assembly, Integration, and Testing (AIT) is a critical phase in satellite manufacturing, ensuring the functionality and reliability of space-bound assets. AIT engineering demands a diverse skill set encompassing system knowledge, procedural expertise, tool proficiency, and safety awareness, among others. However, the high costs and limited availability of required hardware often pose challenges for hands-on training. To address these constraints, Virtual Reality (VR) emerges as a promising solution for AIT training and for training of cleanroom operations in general. By leveraging the immersive capabilities of VR, trainees can engage in realistic simulations of AIT and cleanroom operations, acquiring essential competencies in a cost-effective manner and a controlled environment. This serves as the central concept behind the development of ICARUS, a VR training platform tailored for AIT and cleanroom procedures. Using ICARUS, trainees can develop and improve selected competencies based on actual AIT and cleanroom procedures, digital models of the required components, and a realistic representation of required steps and activities in VR. This includes activities such as cable harnessing and requires a sufficiently realistic representation of all the tooling required in the AIT process, among others. Based on validation experiments with potential ICARUS users, it is concluded that ICARUS is valuable for initial training and familiarization, making it a useful supplement to traditional methods. Indeed, most trainees would feel more confident in completing similar tasks in real-life, after following training in ICARUS.